Influence of Information Sources on Purchase Decisions of Organic Skin Lightening Products among Female Civil Servants in South-East Nigeria - Adum, Nnanwuba Allen; Obi, Evelyn Chinwe (Social Science Research, 2024)
Organic skin-lightening products have gained access to different public domains like the mainstream and various social media platforms. Mix method design such as, survey and in-depth interview was used. The purpose of the study was to investigate the influence that Information sources have on the purchase decisions of organic skin-lightening products among female civil servants in southeast Nigeria. The specific objectives are: To identify the preferred sources of skincare information among female civil servants in southeast Nigeria. And to examine how skincare information sources, influence the purchase decisions of the female civil servants in southeast Nigeria concerning organic lightening skincare products. Using the sample sizes as worked out by Krejcie and Morgan (1970) for different population ranges, a sample of 609 female civil servants was drawn from different ministries, departments and agencies in the South-East geopolitical zone of Nigeria. The study was anchored on the Social Cognitive Theory. The findings of the study revealed that the most influential information sources for female civil servants when making purchase decisions for organic skin-lightening products were family and friends, followed by social media advertisements. The study also found that respondents’ purchase decisions are majorly influenced by convictions through referrals and recommendations from family, friends/associates, and also through online testimonials. It concludes that female civil servants’ purchase decisions are influenced by their preferred sources which are; family/friends and then social media platforms. This study, however, recommends that both the online and offline information sources should be censored, this is necessary to help checkmate products’ false claims that could endanger consumers’ lives and expose them to health risks.